(untitled) (Journal of the Bangladesh Chemical Society, 2013)
Polarity behavior of a hydrophobic ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethyl)sulphonylimide [EMI][TFSI] and binary mixtures of [EMI][TFSI] with ethanol, acetone and dichloromethane was investigated by solvatochromic method using Reichardts betaine dye. Fluorescence spectroscopic method using pyrene as a probe was also used for estimation of polarity of [EMI][TFSI] and [EMI][TFSI]-based binary systems. The binary mixtures of [EMI][TFSI] with the molecular solvents interestingly showed increase in polarity with increasing [EMI][TFSI] for all compositions. The comparative and contrastive features of the results of two methods have been discussed to judge relative merit of one method over the other. Both of the methods collectively provided information to correlate specific interaction of the IL with molecular solvents and define polarity behavior. Journal of Bangladesh Chemical Society, Vol. 25(2), 146-158, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15067